2003
DOI: 10.1001/archsurg.138.11.1198
|View full text |Cite
|
Sign up to set email alerts
|

One Thousand Fifty-Six Hepatectomies Without Mortality in 8 Years

Abstract: Background: Despite improvements in diagnostic and surgical techniques, operative mortality associated with liver resection is still greater than 2% in most of the recent studies. Hypothesis: By refining preoperative and postoperative care and surgical skills, liver resection mortality can be decreased to zero. Design: Retrospective cohort study to analyze postoperative morbidity and mortality in 1056 consecutive hepatectomies performed at a single medical center during 8 years. Setting: Tertiary referral cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
622
5
30

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 783 publications
(689 citation statements)
references
References 60 publications
28
622
5
30
Order By: Relevance
“…In our study mortality rate was zero despite the limited number of patients, and major complications occurred in one patient only. Although numerous studies report a transfusion rate of packed red blood cells below 10% [9,10] or 30% [7,24], in our study 45% of the patients were transfused with packed red blood cells. However, all transfusions were carried out intraoperatively, but study criteria were followed only in one case.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In our study mortality rate was zero despite the limited number of patients, and major complications occurred in one patient only. Although numerous studies report a transfusion rate of packed red blood cells below 10% [9,10] or 30% [7,24], in our study 45% of the patients were transfused with packed red blood cells. However, all transfusions were carried out intraoperatively, but study criteria were followed only in one case.…”
Section: Discussioncontrasting
confidence: 56%
“…US control during the execution of the resection cut permits confirmation or modification of the trajectory in real time, thus making it possible to resort to resection strategies which would otherwise be too difficult or too risky [4,21]. Some authors report an elevated number of cases in which the advanced application of US-guided liver resection decisively contributes to achieving zero postoperative mortality and a major complications rate below 9% [9,10]. In our study mortality rate was zero despite the limited number of patients, and major complications occurred in one patient only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] The risk of mortality increases 5-fold in patients with prior ischemic heart disease undergoing non-cardiac surgery. 7 While advancements in surgery and anesthesia have lead to a dramatic improvement in post-hepatectomy mortality from 20% to nearly 0% over the last 3 decades, [8][9][10] the morbidity associated with complex liver resections remains considerable. In an Italian study evaluating 1500 consecutive patients undergoing hepatectomy, the authors observed a morbidity of 22.5%.…”
Section: Introductionmentioning
confidence: 99%